Spinal and Pelvic Disposition Associated with Utero-Vaginal Prolapse Among Post-Menopausal Women in Chennai (South India) - A Single Blinded Pilot Study - Deepthi, Ganesan; Yu, Chye Wah; Lavanya, Prathap; Pandian, Sankara Kumaran; Kshtrashal, Singh; Prathap, Suganthirababu; Vinodhkumar, Ramalingam (Türkiye Fizyoterapistler Derneği, 2021)
Background: Levatorani muscle and pelvic connective tissues provide primary support to the pelvic organs. Women are predisposed to pelvic organ prolapse due to the weakness of pelvic floor muscles and ligament laxity, which is mostly associated with aging and an increase in intra-abdominal pressure that affects the biomechanical properties of the pelvic tissues. Hence, this study aims to find the correlation between the spinal and pelvis disposition among postmenopausal women with and without utero-vaginal prolapse. Methods: Postmenopausal women who met inclusion and exclusion criteria were randomly selected from Saveetha medical college and hospital inpatient and outpatient departments. Following assessment, the postmenopausal women with prolapse were assigned to Group A and without prolapse to Group B. The participants' angle of lumbar lordosis and pelvic inlet angle calculated in reference to lateral lumbosacral spine x-rays by a radiologist who was blinded for the study. The data were analyzed statistically using the MannWhitney test and Spearman’s correlation test. Results: There is a significant reduction in the lumbar lordotic angle and an increase in pelvic inlet angle in Group A (with prolapse) compared with Group B (without prolapse). Hence, there is an inversely proportional correlation between the lumbar lordosis and pelvic inlet angle. Conclusion: The changes in lumbar lordosis angle and pelvic inlet orientation may cause pelvic floor muscle weakness, which indirectly contributes to utero-vaginal prolapse. This study certainly emphasizes the importance of postural analysis and corrective pelvic floor therapy regimens for women with utero-vaginal prolapse.